2014
DOI: 10.1016/j.ydbio.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RHO–ROCK signaling enhances ICM and suppresses TE characteristics through activation of Hippo signaling in the mouse blastocyst

Abstract: Specification of the trophectoderm (TE) and inner cell mass (ICM) lineages in the mouse blastocyst correlates with cell position, as TE derives from outer cells whereas ICM from inner cells. Differences in position are reflected by cell polarization and Hippo signaling. Only in outer cells, the apical-basal cell polarity is established, and Hippo signaling is inhibited in such a manner that LATS1 and 2 (LATS1/2) kinases are prevented from phosphorylating YAP, a key transcriptional co-activator of the TE-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
151
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 77 publications
17
151
0
Order By: Relevance
“…Incubation of 8-cell embryos in the presence of Y-27632, a specific inhibitor of ROCK1 and ROCK2, blocked blastocyst formation and resulted in a loss of position-dependent HIPPO signaling. These findings are largely consistent with those of a recent study which showed that RHO-ROCK signaling is required for trophectoderm specification (Kono et al, 2014). Specifically, the authors showed that ROCK controls position-dependent HIPPO signaling by repressing LATS activity in the outside cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Incubation of 8-cell embryos in the presence of Y-27632, a specific inhibitor of ROCK1 and ROCK2, blocked blastocyst formation and resulted in a loss of position-dependent HIPPO signaling. These findings are largely consistent with those of a recent study which showed that RHO-ROCK signaling is required for trophectoderm specification (Kono et al, 2014). Specifically, the authors showed that ROCK controls position-dependent HIPPO signaling by repressing LATS activity in the outside cells.…”
Section: Discussionsupporting
confidence: 91%
“…To test whether apical cell polarity was altered in Y-27632-treated embryos, we evaluated the expression and localization of PARD6B. Consistent with a previous report (Kono et al, 2014), PARD6B was no longer largely confined to the apical region, but was localized to both the apical and basal region of the embryos (Fig. 6F).…”
Section: Rock Acts Downstream Of Tfap2c To Repress Hippo Signalingsupporting
confidence: 83%
See 1 more Smart Citation
“…Mechanical force has been proposed to modulate signalling by both the apical Crb-Mer/Ex-Kibra-Sav system in Drosophila (Fletcher et al, 2015;Rauskolb et al, 2014) as well as the basal integrin-Src system in mammalian cell culture (reviewed in Humphrey et al, 2014;Lawson and Burridge, 2014). In the early mouse pre-implantation embryo, cortical tension is higher in outer cells than inner cells, leading to nuclear YAP in outer cells despite the presence of an apical domain (Anani et al, 2014;Kono et al, 2014;Nishioka et al, 2009). Consistently, reducing cortical tension with a ROCK inhibitor abolishes nuclear localisation of YAP in early mouse embryos (Anani et al, 2014;Kono et al, 2014;Nishioka et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This apical protein complex plays important roles in the formation of the blastomere apical domain (Plusa et al, 2005;Alarcon, 2010). Rho GTPase activity and microtubule dynamics are also required for initiating apical domain formation, but how they are linked to the apical protein complex is unknown (Clayton et al, 1999;Houliston et al, 1989;Kono et al, 2014).…”
Section: Experimental Manipulations and Consequencesmentioning
confidence: 99%